2022
DOI: 10.3390/jmmp6050110
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic Material: Effect of Alkyl Chain Length on the Surface Roughness

Abstract: The clean technologies of self-cleaning surfaces are expanding rapidly. Highly hydrophobic coatings with strong adhesion, high durability, and dirt-free surfaces have been prepared via sol-gel deposition of SiO2-TiO2-alkylsilane. The influence of the effects of the alkyl chain length of silane on surface roughness was investigated. This deposition involved a one-layer technique to produce the rough surfaces. The bimetal oxide of SiO2-TiO2 created a high level of surface roughness. As a result, the water contac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…This is supported by earlier studies, which reported that the contact angle decreased after 25 to 30 washings, and the reduction may be due to cracks in silica film on the fibre surface caused by the swelling of cotton [33,47]. The second reason is the absorption of water molecules by OH groups present on the coated surface during long-term direct contact with water [41,42]. Furthermore, any material intended for use as a biomaterial must be biocompatible and must also have a contact angle greater than 120° for at least a week after implantation in order to stop this tissue reaction [13,17].…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This is supported by earlier studies, which reported that the contact angle decreased after 25 to 30 washings, and the reduction may be due to cracks in silica film on the fibre surface caused by the swelling of cotton [33,47]. The second reason is the absorption of water molecules by OH groups present on the coated surface during long-term direct contact with water [41,42]. Furthermore, any material intended for use as a biomaterial must be biocompatible and must also have a contact angle greater than 120° for at least a week after implantation in order to stop this tissue reaction [13,17].…”
Section: Resultssupporting
confidence: 83%
“…In water, hydrogen bonds break easily [40]. In addition, the unreacted OH group present on surface of coated fabric may absorb water molecules physically or by hydrogen bond [41,43]. Additionally, the spectra between 1600 cm −1 and 1700 cm −1 appeared for the sample dipped for 30 days, while the peak between 1600 cm −1 and 1700 cm −1 normally appeared for amine groups [34].…”
Section: Resultsmentioning
confidence: 99%
“…26 The absorption band at 1640 cm −1 is associated to the -OH absorbed on the silica gel surface, which is supported with the board peak at 3600-3400 cm −1 . 27 Increasing the volume of ethanol led to an increase in the intensity of the Si-O-H vibration at 960 cm −1 , demonstrating that the presence of ethanol promotes the hydrolysis process in the reaction. Compared with the IR spectra of LM, the intensity of absorption band at 960 cm −1 of the synthesized silica gel is broader, revealing the formation of the amorphous silica phase.…”
Section: Resultsmentioning
confidence: 94%
“…Py-CSSE demonstrates a shorter D 1 -spacing than CSSE (0.81 nm vs. 0.98 nm), indicating that the incorporation of pyrenyl moieties into Py-CSSE probably prevents the formation of long siloxane chains between each silsesquioxane unit during polymerization and potentially causes a collapsed structure as a result of the self-assembly disorder, resulting in a lower hydrophobicity. 63 The energy dispersive X-ray (EDX) pattern showed the presence of Si, O, and C atoms which can imply the presence of both the SQ cage and pyrene aromatic ring within the polymeric networks (Fig. S11 †).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%